1997
DOI: 10.1002/(sici)1097-0142(19970601)79:11<2219::aid-cncr21>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of BRCA1 testing and reactions to disclosure of test results

Abstract: DNA testing of patients with HBOC syndrome must be performed in the context of genetic counseling. The authors' results demonstrate the many complex clinical and nonclinical issues that are important in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(103 citation statements)
references
References 13 publications
8
91
1
3
Order By: Relevance
“…20,50 FAP is an early-onset disease which may influence testing at a young age, 51 compared with BRCA testing which is typically not recommended before the age of 25 years. 52 A 2009 study showed that less than half of clinics surveyed that perform PGD and require genetic counseling assessed how well patients understood the information disclosed during a counseling session. 53 Thus, one approach to informing highrisk consumers about PGD and the associated risks and benefits may be through the development of standardized protocols to disseminate consistent, accurate information and support patients' psychological concerns.…”
Section: Acceptability Of Pgd Among High-risk Consumersmentioning
confidence: 99%
“…20,50 FAP is an early-onset disease which may influence testing at a young age, 51 compared with BRCA testing which is typically not recommended before the age of 25 years. 52 A 2009 study showed that less than half of clinics surveyed that perform PGD and require genetic counseling assessed how well patients understood the information disclosed during a counseling session. 53 Thus, one approach to informing highrisk consumers about PGD and the associated risks and benefits may be through the development of standardized protocols to disseminate consistent, accurate information and support patients' psychological concerns.…”
Section: Acceptability Of Pgd Among High-risk Consumersmentioning
confidence: 99%
“…12,13,17,20,21,23,24 Indeed, one study showed that individuals with suspected HBOC are initially motivated to undergo genetic testing for the express purpose of generating genetic information for relatives. 13 A conflicting obligation reported is the protection of family from psychological or other harm (such as insurance discrimination 22,41 or causing an upset within the family 20 ) that may arise from this knowledge. 15,18,20,21,31 Thus a primary concern around communication may be at the best interests of relatives; however, the complexity of individual perceptions, familial context and relationships, community and cultural context and of genetic information itself may leave individuals unsure how to meet these best interests.…”
Section: Certainty Of Hboc Genetic Informationmentioning
confidence: 99%
“…4 -6 However, because these reports only assessed psychologic distress using various self-rating questionnaires, it is difficult to compare the rates of clinically significant psychologic distress after a primary diagnosis of sporadic cancer (14 -38%) [7][8][9] or the prevalence of current posttraumatic stress disorder (PTSD) (2.5-6.0%) among breast carcinoma survivors. 10,11 Similarly, although feelings of guilt are a known, specific psychosocial response among individuals undergoing genetic testing, 12,13 previous reports were based on anectodotal experience. 13 Therefore, to our knowledge, no studies to date have investigated the degree or persistence of feelings of guilt in detail after the disclosure of genetic test results.…”
mentioning
confidence: 99%
“…10,11 Similarly, although feelings of guilt are a known, specific psychosocial response among individuals undergoing genetic testing, 12,13 previous reports were based on anectodotal experience. 13 Therefore, to our knowledge, no studies to date have investigated the degree or persistence of feelings of guilt in detail after the disclosure of genetic test results.…”
mentioning
confidence: 99%